Characterization of low-cost Brazilian resin composites submitted to tooth brushing - Marcela Alvarez Ferretti; Renata Pereira; Rodrigo Barros Esteves Lins; Mariana Gusmão Corsini Soares; Larissa Jacó Hessel Pinto; Luís Roberto Marcondes Martins; Flávio Henrique Baggio Aguiar (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: This in vitro study aimed to evaluate surface microhardness, roughness, color, gloss and topography of low-cost Brazilian resin composites, compared with an international one. All 120 samples (8mm ø x 2mm height) were prepared and divided into 5 groups: Ultrafill (Biodinâmica), Llis (FGM), Fill Magic (Coltene), Applic (Makira), and Filtek Z250XT (3M Oral Care). Surface microhardness (KHN) (n=10) was analyzed at two time periods: before and after simulated tooth brushing (STB). Other standardized samples of each group (n=10) were analyzed for surface roughness (Ra), color (ΔL, Δa, Δb, ΔE, ΔE00) and gloss unit (GU) at the same two periods. The topography of non-brushed and brushed samples of each group (n=4) was evaluated by scanning electron microscopy. Data were analyzed statistically by two-way repeated measures ANOVA with Bonferroni post-hoc test (KHN, Ra, GU), and one-way ANOVA with Tukey post-hoc test (ΔL, Δa, Δb, ΔE, ΔE00) (α=0.05). Topographic images were submitted to descriptive analysis. The low-cost Brazilian resin composites investigated were compared with the international one and revealed: lower KHN, regardless of before or after STB; statistically similar Ra before STB, except Ultrafill, which presented higher values; lower Ra after STB, except Ultrafill, which presented statistically similar values; statistically similar color change in ΔL, Δa, Δb parameters; statistically similar color change in ΔE, ΔE00 parameters, except Fill Magic, which presented lower values; lower gloss before STB; lower gloss after STB, except Ultrafill, which presented statistically similar values. In a situation of scarce resources, low-cost Brazilian composites might be an acceptable cost-effective restorative alternative.